Entre la justicia ordinaria y el derecho propio: mujeres indígenas luchando contra el racismo, el patriarcado y la impunidad en Ecuador (Sección Abierta) - Cucurí Miñarcaja, Cristina (2026)
This article explores the complex relationship between indigenous women in Ecuador and state as well as indigenous justice, which is marked by the continuity of colonialism, structural racism and patriarchy. Despite the formal recognition of indigenous justice in the 1998 and 2008 constitutions, gender-based violence continues to disproportionately affect indigenous women, who on the one hand, face multiple barriers to access to ordinary justice. On the other hand, despite the recognition and legitimacy of indigenous justice, it reproduces gender inequalities within community dynamics. In this context, based on a normative analysis accompanied by historical documents -such as the testimonies of Kichwa women in the province of Chimborazo, this research sets out to understand how indigenous women, through community organization, seek to redefine and transform their own justice against patriarchy and colonialism, rescuing ancestral principles and proposing mechanisms to promote territories free of violence. On this basis, it shows that indigenous women find in their own justice a hope for emancipatory, and they are on the way to strengthening it from a gender perspective, which leads community dynamics towards a life of dignity and violence-free.